Global finance and the macroeconomy - Makin, A. J. (Palgrave Macmillan, 2003)
This text provides new ways of analyzing the key issues in international finance and open economy macroeconomics. The topics covered include: financial globalization and the evolution of the international financial system; international macroeconomic accounting and measurement; early balance of payments approaches; the intertemporal model of international borrowing and lending; the significance of external deficits; the determinants of interest rate differentials and exchange rates; the effectiveness of monetary and fiscal policies; capital mobility and economic growth; and the causes of financial crisis in emerging economies.